2018
DOI: 10.1002/nau.23555
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cystoscopy and hydrodistention on symptoms and bladder capacity in interstitial cystitis/bladder pain syndrome

Abstract: Hydrodistention does not decrease bladder capacity even with multiple procedures, and measurably improves symptoms in some patients with IC/BPS. Continuing efforts to better identify those patients most likely to benefit from this procedure are justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…This discussion of flare triggers and related symptoms supports previous work that guides the contemporary evaluation and treatment of men with UCPPS 13,19–25 . Participants in the MAPP focus groups described a wide range of symptom exacerbations, with a significant degree of distress expressed over urinary symptoms in addition to their pain.…”
Section: Discussionsupporting
confidence: 72%
“…This discussion of flare triggers and related symptoms supports previous work that guides the contemporary evaluation and treatment of men with UCPPS 13,19–25 . Participants in the MAPP focus groups described a wide range of symptom exacerbations, with a significant degree of distress expressed over urinary symptoms in addition to their pain.…”
Section: Discussionsupporting
confidence: 72%
“…Multiple studies found worsening symptoms or no statistically significant changes following HD 20,22,23 . This is supported by a study with a large sample size (328 patients), which found no statistically significant changes in pain scores 39 . The concordance between multiple studies concerning the inefficacy of HD suggests this approach may not yield long‐term symptomatic relief in patients with IC/BPS.…”
Section: Discussionmentioning
confidence: 80%
“…The study by Kirk et al 39 had a large sample size of patients suffering from BPS (328 patients) and found a decrease in symptom scores of only 14% and no statistically significant changes in pain. Furthermore, other studies also found symptoms were worsened or observed no statistically significant changes in symptoms following hydrodistension (HD) 20,22,23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among lower urinary tract symptoms, patients commonly misinterpret urinary urgency as pain or fear of urinating unintentionally, but this is also not a requirement for diagnosis. Again, current bladder-related pain and discomfort are the primary and essential diagnostic requirements [16][17][18][19][20][21][22][23][24][25].…”
Section: Considering Points For the Diagnosis Of Interstitial Cystiti...mentioning
confidence: 99%